Development and psychometric evaluation of the nurse behavior toward confirmed and suspected HIV/AIDS patients (NB-CSHAP) scale - De los Santos Janet Alexis; Milla Norberto; Tuppal Cyruz; Labrague Leodoro (Sciendo, 2022)
There is a scarcity of literature discussing nurses' behaviors toward caring for suspected or confirmed human immunodeficiency virus (HIV)/acquired immunodeficiency syndrome (AIDS) patients. The development of a scale specific to measure nurses' behaviors will allow health institutions to assess the disposition of their nurses in terms of HIV care. This study aims to present the rigors of developing and validating a reliable instrument to contextualize these nurses' behaviors. This study utilized a sequential exploratory mixed method design to develop the NB-CSHAP scale. Thematic analysis was done on the qualitative data from the interviews with persons living with HIV/AIDS (PLHA) from which items were selected to be included in the scale. Exploratory factor analysis was utilized to extract the factors and Cronbach's alpha was used to assess the reliability of the instrument. Four factors were extracted and are categorized as either caring or discriminatory behaviors. These include: (1) service-oriented, (2) openhanded, (3) perceptive, and (4) discriminatory. The scale has an internal consistency of 0.73. The scale shows acceptable psychometric properties, hence can be used to assess the nurses' behaviors in caring for confirmed or suspected HIV clients. The scale may be used by health institutions to determine the quality of the patient care provided by their nurses to clients with confirmed or suspected HIV.